Pressure effect on electronic and optical properties of noncentrosymmetric LaPtGe3 studied by ab initio method - Md. Karimul Islam; Nilufer Yesmin Tanisa; Mosfiqur Rahman; Abul Monsur Musa; Tareque Aziz; Md. Moiful Alam; Asif Pervez (AIP Advances)
Density functional theory applied with the CASTEP algorithm was used to evaluate the electrical and optical characteristics of LaPtGe3. The band structure reveals overlapping bands at the Fermi level, indicative of metallic behavior, with Ge-4p states playing a dominant role in electrical conductivity. Pressure-induced changes in the density of states and Ge–Ge bond lengths suggest a significant influence on the optical and thermodynamic properties of LaPtGe3. Reflectivity increases under external pressure, exhibiting anisotropic behavior along the crystallographic axes, particularly around 17 eV along the [001] direction. Absorption spectra show a metallic response starting from zero photon energy, with maximum absorption near 20.50 eV and transparency beyond 50 eV. Increased pressure enhances absorption, making the material more viable for solar cell applications under high pressure. Photoconductivity also begins at zero photon energy, confirming the absence of a bandgap. The anisotropic nature is evident in absorption and conductivity spectra across all pressure ranges. The bulk plasma frequency, measured at 25.65 eV, increases with pressure, while the refractive index shows a high initial value followed by a decline in the infrared, visible, and ultraviolet regions. The components of the dielectric function’s real (ε1) and imaginary (ε2) confirm metallic characteristics. These findings highlight the potential of LaPtGe3 for applications in optoelectronics and high-pressure environments.